A CASE REPORT OF NADROPARIN INDUCED HYPERKALEMIA - O, Balaji; Chogtu, Bharti; Patil, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Nadroparin, a low molecular weight heparin, has prophylactic and therapeutic use in thromboembolic disorder. In a patient with carcinoma ovary stage 3 B, nadroparin was given prophylactically for deep vein thrombosis (DVT) before and after interval cytoreduction surgery. Nadroparin 0.3 ml was given subcutaneously once daily for 1 day preoperatively and 8 days postoperatively. Rise in serum potassium was observed on the third postoperative day suggestive of hyperkalemia. Intravenous fluids were given, and the drug was stopped on the 9 post-operative day and hyperkalemia resolved after 2 days. Monitoring of serum potassium level is essential when Nadroparin is administered prophylactically for more than 7 days for DVT. As this case illustrates a causal relationship between nadroparin and hyperkalemia, caution must be exercised with nadroparin. Keywords: Nadroparin, Hyperkalemia, Thrombosis. th